Nijigahara holograph - Asano, Inio, 1980- (Fantagraphics Books, 2014)
"Butterflies ominously proliferate as children whisper rumors of a mysterious creature lurking in the tunnel behind the school. To appease its wrath, they decide to offer it a sacrifice--a human one. But this is only the beginning of Nijigahara Holograph, which takes place in two separate timelines and involves the suicidal Amahiko; Kohta, the lovestruck bully; their teacher Miss Sakaki, whose heavily bandaged face remains a mystery; and many more brothers, sisters, parents, co-workers, teachers, aggressors and victims who are all inextricably linked to one another. Ten years later, all will have to face what they've done or suffered through--and maybe the end of the world."-page [4] of cover.